Simulating graphene oxide nanomaterial phototransformation and transport in surface water. Issue 1 (23rd November 2018) - Han, Yanlai; Knightes, Christopher D.; Bouchard, Dermont; Zepp, Richard; Avant, Brian; Hsieh, Hsin-Se; Chang, Xiaojun; Acrey, Brad; Matthew Henderson, W.; Spear, Jessica
Abstract : The production of graphene-family nanomaterials (GFNs) has increased appreciably in recent years. Abstract : The production of graphene-family nanomaterials (GFNs) has increased appreciably in recent years. Graphene oxide (GO) has been found to be the most toxic nanomaterial among GFNs and, to our knowledge, no studies have been conducted to model its fate and transport in the environment. Lab studies show that GO undergoes phototransformation in surface waters under sunlight radiation resulting in formation of photoreduced GO (rGO). In this study, the recently updated Water Quality Analysis Simulation Program (WASP8) is used to simulate time-dependent environmental exposure concentrations of GO and its major phototransformation product, rGO, for Brier Creek, GA, USA at two flow scenarios under a constant loading of GO to the river for a period of 20 years. Analysis shows that the degree of phototransformation is closely associated with river flow condition: up to of 40% of GO undergoes phototransformation at low flow condition, whereas only 2.5% of GO phototransformation occurs at mean flow condition. River flow and heteroaggregation exhibit a 'competing' effect in determining the formation of rGO heteroagglomerates. Mass fraction analysis indicates that the vast majority of rGO heteroagglomerates settle to the sediment layers due to the settling of suspended solids. Simulation of natural recovery after removal of the GO source suggests that free GO and rGO are the immediate contaminants of concern in the studied surface water system, while rGO heteroaggregated with suspended solids can have a long-term ecological impact on both the water column and sediments.